Methane in the Sediments of a Subarctic Continental Shelf - Vilks, G.; Rashid, M. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Abstract The unconsolidated sediments off eastern Canada contain interstitial methane up to 22,000 ppm. The presence of methane is associated with anoxic conditions found in fine sediments deposited in small basins. The foraminiferal assemblages and Carbon-14 dating of the gaseous deposits indicate rapid rates of sedimentation.